Outcome of routine histo-pathological examination of gallbladder specimen followed by Elective Laparoscopic Cholecystectomy, Ghorahi, Dang, Nepal (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Gall bladder disease is the one of the commonest surgical diseases which is encountered in the surgical department. Gall bladder stone is the commonest pathological condition which affects the gallbladder. Gallbladder carcinoma is a rare but highly lethal malignancy. Gallbladder carcinoma is highly challenging for the health care professionals. This study evaluated the outcome of the routine histopathological examination of laparoscopic cholecystectomy specimens.Materials and Methods: This study was a retrospective observational study, conducted on 209 patients, who had undergone cholecystectomy for the symptomatic cholecystitis at Gorkha Public Hospital Pvt Ltd, General Surgery Department from September 2023 to September 2024. After obtaining ethical clearance from the Institutional Review Committee, the data was retrieved from the hospital records.Results: Of the 209 patients, 80.9% (n=169) were females. Amongst the various histopathological findings, chronic cholecystitis was the most prevalent (71.8%, n=150/209), which was followed by chronic cholecystitis with cholesterolosis (23.0%, n=48/209). All the pathological specimens represented benign conditions except for one which was a 50-years-old female diagnosed with adenocarcinoma.Conclusion: Chronic cholecystitis was the commonest gallbladder pathology with females having higher preponderance for development. Studies are required to elicit further information in this important surgical entity.